Analisis Efisiensi dan Efektivitas Kinerja Pelayanan Pada Perusahaan Air Minum (PDAM) Tirta Agara Kutacane - Muridha Hasan (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2022)
This study aims to analyze the efficiency and effectiveness of service performance at the Tirta Agara Kutacane Drinking Water Company (PDAM). The subject of this research is the Regional Drinking Water Company (PDAM) Tirta Kutacane, while the object of the research is the Customers of the Regional Drinking Water Company (PDAM) Tirta Kutacane. This study uses a qualitative descriptive method, with the method of observation and interview. Research results In general, the performance appraisal of the employees of the Tirta Agara Kutacane Regional Water Company that has been carried out by the leadership includes, among others, performance appraisal based on behavioral assessment, performance appraisal based on the individual characteristics and characteristics of employees, performance appraisal based on work results, performance appraisal on the basis of a combination of several elements,. From the results of the study, it can be concluded that the efficiency, effectiveness of the service performance of the regional drinking water company Tirta Agara Kutacane has not shown maximum results because it is not in accordance with what is expected. natural resources to optimize public services. For the survival of the company to be better, attention is needed from the government both in the form of capital and policies so that service performance will increase.